Inclusion in practice: a systematic review of diversity-focused STEM programming in the United States - Olivia Palid; Sarah Cashdollar; Sarah Deangelo; Chu Chu; Meg Bates (SpringerOpen, 2023)
Abstract Colleges across the United States have shown a commitment to advancing diversity in the STEM fields by creating programs aimed at improving outcomes of women and/or racially and ethnically minoritized students. However, most existing literature focuses on the successes of singular college programs rather than comparing these STEM interventions across the higher education landscape. This systematic review investigates the literature on diversity-focused "STEM intervention programs" (SIPs) at the postsecondary level. We categorize key features of these programs and their outcomes, and we look at which program components have the most empirical support. We examine 82 articles that reported on SIPs with disaggregated outcomes, coding each initiative's features and outcomes. Across these articles, we found six common program components, with most programs including more than one component, and five common program outcomes. Just 53 articles tested differences in outcomes of participants relative to a comparison group. This subset of research found support for the effectiveness of all coded components for improving student outcomes, though studies of multi-component programs did not parse the relative contributions of each component. Based on these findings, we conclude multi-component interventions that create a welcoming environment and focus on the successes of minoritized students help redress existing institutional shortcomings and are a promising step towards diversity, equity, and inclusion in STEM. However, more rigorous quantitative studies are needed to empirically assess the effectiveness of individual SIP program components.